919. Understanding Intermittent Detection of Multidrug-Resistant Organisms (MDROs) in Rectally Colonized Patients. (31st December 2020) - Sansom, Sarah; Lin, Michael Y; Schoeny, Michael; Fukuda, Christine; Bassis, Christine; Shimasaki, Teppei; Dangana, Thelma E; Moore, Nicholas M; Yelin, Rachel; Liu, Sophia; Young, Vincent B; Rhee, Yoona; et al.
Abstract: Background: MDRO detection in colonized patients may be intermittent for reasons that are incompletely understood. We examined temporal patterns of gut MDRO colonization after initial MDRO detection by rectal swab screening, and determined the relationship of culture positivity to the relative abundance of corresponding MDRO operational taxonomic units (OTUs) identified by 16S rRNA gene sequence analysis. Methods: Rectal or fecal swabs were collected daily from MICU patients 1/11/2017-1/11/2018. First MICU admissions with ≥2 swabs and MICU stays ≥3 days were studied. Samples were cultured for vancomycin-resistant enterococci (VRE), carbapenem-resistant Enterobacteriaceae (CRE) and P. aeruginosa (CRPA), and extended-spectrum β-lactamase-producing (ESBL) Enterobacteriaceae by selective media. Resistance mechanisms were confirmed by phenotypic methods and/or PCR. Limit of detection was similar for different MDROs (24-52 CFU/sample). OTU categories corresponding to MDRO species were identified by taxonomy and BLAST. Multilevel regression models estimated the association between MDRO detection and relative abundance of the corresponding OTU. Results: 796 unique patients with 3519 swabs were studied. Median (IQR) age was 64 (51-74) years, MICU length of stay was 5 (3-8) days, and number of samples-per-patient was 3 (2-5). Following initial MDRO detection, the probability of subsequent detection varied by MDRO type, and was highest for VRE and lowest for CRPA [Figure 1]. Within each sample, we found a significant association between MDRO detection and relative abundance of the corresponding OTU [Table 1]. In contrast, relative OTU abundance in the first sample with MDRO detection was not predictive of odds of future MDRO detection (p >0.05 for all comparisons). Carriage of >1 MDRO did not affect the odds of MDRO detection in later samples. Figure 1. Probability of Subsequent MDRO Detection after First Positive Varies by MDRO Type Table 1. Higher Mean Corresponding OTU Relative Abundance Within Each Sample is Associated with MDRO Detection Conclusion: MDRO culture positivity in rectally colonized patients was correlated with relative abundance of the corresponding OTU in the same sample. Serial detection of different MDRO types was variable, possibly due to distinct microbial community dynamics of different MDRO types. Intermittent failure to detect MDROs could result in misattribution of MDRO acquisition, resulting in inappropriate investigation or intervention. Disclosures: All Authors : No reported disclosures